(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
In this paper, we present an estimate for the Fekete-Szegö inequality in the subclass which is defined by Frasin. This estimate led to improving the bound of the third coefficient in this subclass and in the subclass .